Dialectical behaviour therapy 'Skills for Living' for young people leaving care: A qualitative exploration of participants' experiences. (April 2022) - Rouski, Charlene; Yu, Sinitta; Edwards, Amanda; Hibbert, Lisa; Covax, Andi; Knowles, Susan Frances; Wah, Andrew
It is acknowledged that care leavers experience an accelerated transition into adulthood, despite often having complex psychosocial needs with limited support networks. The 'Skills for Living' programme was designed to improve the psychological wellbeing of care leavers and offers an adapted Dialectical Behaviour Therapy skills group as its primary intervention. This paper provides a qualitative evaluation of the programme. Semi-structured interviews were undertaken with 10 participants, and the data were analysed using thematic analysis (Braun & Clarke, 2006 ). Four key themes emerged: 'Initial Apprehension and Reluctance to Participate', 'Connection, Understanding and Validation', 'Confidence with Social Skills', and 'Emotional Acceptance and Self-Soothing'. Clinical implications and recommendations are discussed.